Improving Train Services To Increase Student Mobility And Safety On The Purwakarta-Karawang Route - Martin, Marchanda Rahmawati; Ulfa, Vina Syofiyatul; Sari, Dessy Agustina (Jurnal Penelitian Sekolah Tinggi Transportasi Darat, 2024)
Transportation is essential for the mobility of workers and students, yet many prefer motorcycles over public transportation like trains due to inadequate schedules and limited train availability. This choice contributes to Indonesia's high motorcycle usage and associated traffic accident risks. This study focuses on the Purwakarta-Karawang train route and its impact on student mobility at Universitas Singaperbangsa Karawang. Employing a qualitative method with descriptive data collection and SWOT analysis, this research gathers student feedback on current train schedules and their impact on daily commutes. Findings indicate that increasing the number of train schedules could significantly improve student mobility and reduce the reliance on motorcycles, thereby decreasing traffic accidents. Moreover, better train schedules could enhance access to educational and employment opportunities. The study suggests that the local government should consider expanding and optimizing train services to address these issues. This research contributes to the broader field of transportation studies by highlighting the importance of efficient public transport schedules in reducing traffic accidents and supporting student mobility. It emphasizes the need for policy adjustments to improve Indonesia's public transportation infrastructure and services by proposing practical solutions.